Gas phase aldehyde hydrogenation catalyst and preparation method thereof

Through acid-base co-precipitation method and calcination, the specific pore size and active metal dispersion of gas-phase aldehyde hydrogenation catalysts are improved, and the diffusion and activity of existing catalysts are solved, and more efficient catalytic performance is achieved.

CN114054033BActive Publication Date: 2025-02-28PETROCHINA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202010769657.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-03
Publication Date
2025-02-28
Estimated Expiration
2040-08-03

AI Technical Summary

Technical Problem

The existing gas-phase aldehyde hydrogenation catalysts have insufficient diffusion performance in the reaction material inside the catalyst, and poor dispersion of active metal components, resulting in low catalytic activity.

Method used

The catalyst was prepared by acid-base co-precipitation method. The complexation of citric acid and metal salt and the precipitation of carbonate were improved, and the specific table pore size of the catalyst was increased by calcining and graphite tableting molding.

Benefits of technology

The specific pore size of the catalyst and the diffusion performance of the reaction material are significantly improved, the dispersion of the active metal components is enhanced, and the activity and selectivity of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalysts, and specifically discloses a gas-phase aldehyde hydrogenation catalyst and a preparation method thereof. The preparation method adopts an acid-base two-step precipitation method to increase the specific surface pore size of the catalyst and improve the internal diffusion performance of the reaction material, and at the same time adopts inorganic modification to improve the dispersion performance of the active component. The preparation method roasts the catalyst sample after molding, and the obtained gas-phase aldehyde hydrogenation catalyst composition includes the following substances in percentage by weight: 30% to 40% copper oxide, 55% to 70% zinc oxide, 0.1% to 6% aluminum oxide, 1% to 3% graphite, 0.1% to 5% magnesium oxide, and 0.05% to 2% silicon oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and particularly relates to a gas-phase aldehyde hydrogenation catalyst and a preparation method thereof. Background Art

[0002] The catalysts used in gas-phase aldehyde hydrogenation mainly include copper-chromium (Cu-Cr) catalysts and copper-zinc (Cu-Zn) catalysts. The main active component in the catalyst is copper. With the increasing requirements for environmental protection, since the mid-1990s, catalysts with Cu-Zn as the active component have gradually replaced Cu-Cr catalysts. Compared with Cu-Cr catalysts, Cu-Zn catalysts have the characteristics of less pollution, longer life and higher mechanical strength. In the Cu-Zn catalyst, copper is the active component, and ZnO acts as a carrier and auxiliary agent. The main companies developing Cu-Zn catalysts abroad are UCC in the United States, ICI in the United Kingdom, Engelhard in the United States, Hules in Germany, and Hoechst in Germany. Cu-Zn catalysts are generally prepared by co-precipitation, and the obtained metal oxide powder is pressed into a cylindrical catalyst. Aluminum is more commonly used as an auxiliary agent, and Al in the catalyst 2 O 3 The content is generally 1% to 10%. The gas-phase aldehyde hydrogenation catalysts used in China mainly include OXO-1 / OXO-2 gas-phase aldehyde hydrogenation catalysts developed by Clariant, VAH-1 / VAH-2 gas-phase aldehyde hydrogenation catalysts developed by Sinopec Petrochemical Research Institute, NCH6-1 butyraldehyde gas-phase hydrogenation catalysts and NCH6-2 octenal gas-phase hydrogenation catalysts developed by Sinopec Nanfang Chemical Research Institute. These catalysts are all Cu-Zn catalysts, prepared by coprecipitation method, and the catalyst molding method is tablet molding method. The bulk density of OXO catalyst is 1.30-1.40g / ml, the bulk density of VAH catalyst is 1.45-1.60g / ml, and the bulk density of NCH6 catalyst is 1.45-1.60g / ml.

[0003] Union Carbide Corporation of the United States has announced an aldehyde hydrogenation catalyst CN1050994A, which is mainly composed of a mixture of impregnated improved copper and zinc oxide, and uses selectivity improvers such as sodium, potassium, and lithium. The catalyst has good selectivity, but the patent does not disclose the physical properties of the catalyst, and the patent has expired.

[0004] Chinese patents CN1381311A and CN1381312A disclose a method for preparing a gas-phase aldehyde hydrogenation catalyst by using a mixed solution of copper, zinc and aluminum nitrates and a precipitant for coprecipitation reaction, and then adding a small amount of an auxiliary agent. The obtained catalyst has high low-temperature activity, selectivity and stability. However, due to the fact that Cu 2+ With Al2 O 4 2- Pre-combined, easy to form stable CuAl 2 O 4 The spinel structure reduces the amount of reducible metallic copper, thereby reducing the activity of the catalyst.

[0005] Chinese patent CN102350360A discloses that Sinopec Nanhua Research Institute has proposed a highly liquid-resistant aldehyde hydrogenation catalyst, and the preparation method adopts a secondary roasting process to improve the catalyst's anti-immersion ability. Although this process improves the catalyst's anti-immersion ability, the secondary roasting causes a decrease in the catalyst's specific surface area and pore volume.

[0006] Chinese patent CN1695802A discloses that Tianjin Chemical Research and Design Institute prepares a copper-zinc gas-phase aldehyde hydrogenation catalyst and preparation method by adding special metal additives for modification. Since an intermittent feeding method of zinc and additive co-precipitation and copper-zinc co-precipitation in steps is adopted and special metal element additives are added for modification, the prepared catalyst has the characteristics of good alcohol selectivity. However, since the preparation process of the copper-zinc-aluminum catalyst matrix cannot achieve continuous operation but simple mechanical mixing, the preparation process is complicated and the repeatability is poor. The catalyst grain size is uneven and the dispersion of active metal copper is not high.

[0007] Chinese patent CN108043411A discloses a catalyst for preparing n-butanol by hydrogenation of n-butyraldehyde and its preparation method by Yantai Wanhua Chemical. The catalyst comprises copper oxide, zinc oxide and silicon dioxide. The preparation method of the catalyst adopts a synchronous precipitation method to precipitate copper and zinc at two different temperatures respectively, to obtain two different pore structures, and to form a dual pore system.

[0008] Chinese patent CN106132542A discloses a method for forming a Cu-Zn catalyst body by Clariant. The method uses zinc oxide as a raw material and its calcination temperature is 280°C, which is significantly different from other patents. Low-temperature calcination is conducive to metal dispersion, but low temperature can easily cause incomplete decomposition of carbonates.

[0009] Chinese patent CN102407122B discloses a method for preparing an octenal gas-phase hydrogenation catalyst from the Northwest Institute of Chemical Technology. The process adopts step-by-step continuous co-precipitation, and the selectivity of the catalyst prepared by this method is relatively low.

[0010] Chinese patent CN106582660 discloses a method for preparing an aldehyde hydrogenation catalyst, which is prepared by adding copper salt and zinc salt to an aqueous solution of nano-alumina through coprecipitation. A pore-forming agent or an alkaline pore-forming agent is added to improve diffusion performance. The catalyst prepared by this method has low conversion rate and selectivity.

[0011] Catalyst preparation mainly includes co-precipitation, aging, drying, roasting, tableting and other processes. Metal composition, powder processing effect and tableting process conditions will affect the bulk density of the catalyst. The key technical issues that need to be solved are:

[0012] Improve the diffusion performance of the reaction materials inside the catalyst, optimize the catalyst metal composition, and improve the dispersion of active metal components. Summary of the invention

[0013] The object of the present invention is to provide a method for preparing a gas-phase aldehyde hydrogenation catalyst, thereby increasing the specific pore size of the catalyst, improving the internal diffusion performance of the reaction material, and simultaneously using inorganic modification to improve the dispersion performance of the active component.

[0014] To achieve the above object, the preparation method of the gas-phase aldehyde hydrogenation catalyst of the present invention adopts an acid-base coprecipitation method and comprises the following steps:

[0015] (1) adding a mixed solution of zinc nitrate, aluminum nitrate, copper nitrate, magnesium nitrate and silica sol and a precipitant A into a reactor in parallel, neutralizing and aging for 25 to 35 minutes in a reactor kept at 60 to 70° C. and stirred to obtain an aged solution;

[0016] (2) without removing the mother liquor, the aged solution obtained in step (1) and the precipitant B are directly added to the same reactor in parallel for neutralization and aging again to form a coprecipitation solution;

[0017] (3) The coprecipitation solution of step (2) is washed with water and filtered to obtain a filter cake, the filter cake is dried and calcined, and finally graphite is added to form a sheet to obtain a gas-phase aldehyde hydrogenation catalyst.

[0018] The method for preparing a gas-phase aldehyde hydrogenation catalyst of the present invention, wherein the molar ratio of zinc nitrate, aluminum nitrate, copper nitrate, magnesium nitrate and silica sol in step (1) is 10-25:10-30:1-3:0.1-1:1-3.

[0019] The preparation method of the gas phase aldehyde hydrogenation catalyst of the present invention, wherein the precipitant A is citric acid, and the added amount thereof is 30% to 100% of the stoichiometric amount required for forming citrate with the added zinc nitrate, aluminum nitrate, copper nitrate and magnesium nitrate.

[0020] In the method for preparing a gas-phase aldehyde hydrogenation catalyst of the present invention, the precipitant B is a soluble carbonate, and the amount of the precipitant B added is adjusted to a pH value of 7 to 8 according to the solution in step (2).

[0021] The method for preparing a gas-phase aldehyde hydrogenation catalyst of the present invention, wherein in step (3), the drying temperature is 100 to 120° C., and the drying time is 2 to 4 hours.

[0022] The method for preparing a gas-phase aldehyde hydrogenation catalyst of the present invention comprises the following steps: in step (3), the calcination temperature is 360-380° C. and the calcination time is 3-4 hours.

[0023] The present invention also provides a gas-phase aldehyde hydrogenation catalyst prepared according to the above preparation method, wherein the components of the gas-phase aldehyde hydrogenation catalyst are: 30% to 40wt% of copper oxide, 55% to 70wt% of zinc oxide, 0.1% to 6wt% of aluminum oxide, 1% to 3wt% of graphite, 0.1% to 5wt% of magnesium oxide, and 0.05% to 2wt% of silicon oxide.

[0024] The BET specific surface area of ​​the gas phase aldehyde hydrogenation catalyst of the present invention is 30 m 2 / g~70m 2 / g, the pore volume is 0.15ml / g~0.8ml / g, and the average pore radius is 5nm~20nm.

[0025] The present invention can also be described in detail as follows:

[0026] The method adopts an acid-base two-step precipitation method to prepare the catalyst, and the formed catalyst sample is calcined. The mass of the catalyst is mainly composed of the following substances in percentage by weight: copper oxide is 30% to 40%, zinc oxide is 55% to 65%, aluminum oxide is 0.1% to 6%, graphite is 2%, magnesium oxide is 0.1% to 5%, and silicon oxide is 0.05% to 2%.

[0027] The preparation method is as follows:

[0028] (1) adding a mixed solution of zinc nitrate, aluminum nitrate, copper nitrate, magnesium nitrate and silica sol and a precipitant A into a reactor in parallel, neutralizing and aging for 25 to 35 minutes in a reactor kept at 60 to 70° C. and stirred;

[0029] (2) without removing the mother liquor, the mixed solution of step (1) and the precipitant B are directly added to the same reactor in parallel for neutralization and aging again to form a co-precipitate;

[0030] (3) washing with water, filtering, drying and calcining the obtained filter cake; and finally adding graphite to form a sheet to prepare a gas-phase aldehyde catalytic hydrogenation catalyst;

[0031] (4) The catalyst prepared by the method of the present invention mainly comprises: 30% to 40% copper oxide, 55% to 70% zinc oxide, 0.1% to 6% aluminum oxide, 1% to 3% graphite, 0.1% to 5% magnesium oxide, and 0.05% to 2% silicon oxide;

[0032] (5) The BET specific surface area of ​​the prepared catalyst is 30 m 2 / g~70m2 / g, the pore volume is 0.15ml / g~0.8ml / g, and the average pore radius is 5nm~20nm.

[0033] The invention adopts an acid-base two-step precipitation method, firstly complexing the metal component with citric acid, and then precipitating the metal with carbonate, and the two-step precipitation method is used to improve the dispersion of active metals and increase the number of active centers. DETAILED DESCRIPTION

[0034] The following embodiments of the present invention are described in detail. The following embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually based on conventional conditions.

[0035] Example 1

[0036] (1) 117 g of copper nitrate, 220 g of zinc nitrate, 10 g of aluminum nitrate, 4 g of magnesium nitrate and 6 g of silica sol are prepared into a mixed solution of 1500 ml, and the mixed solution and a citric acid solution with a weight percentage of 15.5% are added into a neutralization tank with heat preservation and stirring for aging, and the neutralization temperature is controlled at about 60°C;

[0037] (2) adding the solution obtained in step (1) and a 25.5% by weight sodium carbonate solution into the same tank in parallel, neutralizing them under stirring, adjusting the solution pH to 7-8 with sodium carbonate, and aging for 1 hour;

[0038] (3) The filter cake was washed four times with deionized water at 40-50°C, dried at 120°C for 2h, calcined at 380°C for 4h, and then added with 2% of the total mass of graphite to obtain catalyst CA-1.

[0039] Example 2

[0040] (1) 125 g of copper nitrate, 215 g of zinc nitrate, 10 g of aluminum nitrate, 4 g of magnesium nitrate and 6 g of silica sol are prepared into a mixed solution of 1500 ml, and the mixed solution and a 15% by weight citric acid solution are added into a neutralization tank with heat preservation and stirring for aging, and the pH is controlled to be 1-2 and the neutralization temperature is controlled to be around 60°C;

[0041] (2) adding the solution obtained in step (1) and a 25.5% by weight sodium carbonate solution into the same tank in parallel, neutralizing them under stirring, adjusting the solution pH to 7-8 with sodium carbonate, and aging for 1 hour;

[0042] (3) The filter cake was washed four times with deionized water at 40-50°C, dried at 120°C for 2h, calcined at 380°C for 4h, and then added with 2% of the total mass of graphite to obtain catalyst CA-2.

[0043] Example 3

[0044] (1) 120 g of copper nitrate, 210 g of zinc nitrate, 10 g of aluminum nitrate, 5 g of magnesium nitrate and 6 g of silica sol are prepared into a mixed solution of 1500 ml, and the mixed solution and a 15% by weight citric acid solution are added into a neutralization tank with heat preservation and stirring for aging, and the pH is controlled to be 1-2 and the neutralization temperature is controlled to be around 60°C;

[0045] (2) adding the solution obtained in step (1) and a 25.5% by weight sodium bicarbonate solution into the same tank in parallel, neutralizing under stirring, adjusting the solution pH to 7-8 with sodium carbonate, and aging for 1 hour;

[0046] (3) The filter cake was washed four times with deionized water at 40-50°C, dried at 120°C for 2 h, calcined at 380°C for 4 h, and then added with 2% of the total mass of graphite to obtain catalyst CA-3.

[0047] Comparative Example 1

[0048] In this comparative example, reference catalyst 1 was prepared by the method of Chinese patent publication CN 1050994A.

[0049] 16 liters of a solution containing 417 grams of copper (added in the form of copper nitrate) and 858 grams of zinc (added in the form of zinc nitrate) was heated to about 43°C and sprayed into a 15.7wt% sodium carbonate solution under mechanical stirring and constant temperature at 60°C. The final pH value of the precipitated mixture was 7.9-8.5. After precipitation, the copper-zinc basic carbonate was filtered and then pulped and washed with deionized water at 37.8-48.8°C. The filtration and pulping were repeated four times to reduce the sodium content in the calcined filter cake to 0.1-0.15wt%. After drying and calcination, a mixture of copper oxide and zinc oxide was obtained. The catalyst matrix was mixed evenly with an appropriate amount of graphite, pressed into tablets, and finally reduced to obtain the reference catalyst CB-1.

[0050] Comparative Example 2

[0051] (1) 117 g of copper nitrate, 220 g of zinc nitrate, 10 g of aluminum nitrate, 4 g of magnesium nitrate and 6 g of silica sol are prepared into a mixed solution of 1500 ml, and the mixed solution and a citric acid solution with a weight percentage of 15.5% are added into a neutralization tank with heat preservation and stirring for aging. The amount of citric acid solution is added at 1.1 times the stoichiometric ratio, and the neutralization temperature is controlled at about 60°C;

[0052] (2) The filter cake was washed four times with deionized water at 40-50°C, dried at 120°C for 2h, calcined at 380°C for 4h, and then added with 2% of the total mass of graphite to obtain catalyst CB-2.

[0053] The physical properties of the catalysts prepared in the above examples and comparative examples are listed in Table 1.

[0054] Table 1 Physical properties of catalysts in Examples and Comparative Examples

[0055] Carrier ZA-1 ZA-2 ZA-3 ZB-1 ZB-2 ZB-3 Pore ​​volume (ml / g) 1.25 1.23 1.22 1.0 0.9 0.71 <![CDATA[Specific surface area (m 2 / g)]]> 280 278 277 210 206 178 Average pore size (nm) 16.1 15.7 15.8 10.4 10.8 9.8 <5nm ratio (%) 20 21 22 35 30 58 5nm~20nm ratio (%) 49 48 47 35 25 20 >60nm ratio (%) 31 31 31 30 34 25

[0056] It can be seen from Table 1 that the pore size of the catalyst modified by pore expansion is significantly larger than that of the unmodified catalyst. The large pore size is conducive to the diffusion of reactants inside the catalyst. When the pores of the catalyst are small, trimers and heavy components in the reactants have large molecular weights, making it difficult to achieve effective hydrogenation.

[0057] The catalytic hydrogenation performance results of octenal in various examples and comparative examples are shown in Table 2.

[0058] The evaluation was conducted on a 200 ml fixed bed hydrogenation evaluation device. The reduction conditions were: hydrogen reduction, reduction temperature 205°C, reduction time 6 hours, and nitrogen cooling after the reduction. The evaluation conditions were: the raw material was industrial octenal, the feed temperature was 160°C, the volume ratio of hydrogen to octenal was 8000:1, and the reaction space velocity was 0.35h -1 , the reaction pressure is 0.45Mpa.

[0059] Table 2 Octenal catalytic hydrogenation performance

[0060] project CA-1 CA-2 CA-3 CB-1 CB-2 Octenal conversion rate (wt%) 99.99 99.98 99.98 99.67 99.67 Octanol selectivity (%) 99.85 99.83 99.84 98.60 99.62

[0061] The catalytic hydrogenation performance results of n-butyraldehyde of the examples and comparative examples are shown in Table 3.

[0062] Experimental process conditions: the raw material is industrial n-butyraldehyde, the feed temperature is 125°C, the volume ratio of hydrogen to n-butyraldehyde is 8000:1, and the reaction space velocity is 0.35h -l , the reaction pressure is 0.45Mpa.

[0063] Table 3 Catalytic hydrogenation performance of n-butyraldehyde

[0064] project CA-1 CA-2 CA-3 CB-1 CB-2 Butyraldehyde conversion rate (wt%) 99.99 99.98 99.98 99.67 99.72 n-Butanol selectivity (%) 99.81 99.80 99.79 99.62 99.69

[0065] As can be seen from the results of Tables 1-3, the catalyst prepared by the method of the present invention has higher octenal conversion and octanol selectivity than the comparative catalyst. The catalyst hydrogenation performance of n-butyraldehyde also has the same rule, and the modified catalyst has the advantage of high strength after activation. Under the same process conditions, the catalyst prepared by the present invention has better octenal and n-butyraldehyde conversion.

Claims

1. Use of a gas-phase aldehyde hydrogenation catalyst in the catalytic hydrogenation of octenal or n-butyraldehyde, characterized in that: The components of the gas-phase aldehyde hydrogenation catalyst are as follows: 30% to 40% by weight of copper oxide, 55% to 70% by weight of zinc oxide, 0.1% to 6% by weight of aluminum oxide, 1% to 3% by weight of graphite, 0.1% to 5% by weight of magnesium oxide, and 0.05% to 2% by weight of silicon oxide. The sum of the mass percentages of the components in the gas-phase aldehyde hydrogenation catalyst satisfies 100% by weight. The gas-phase aldehyde hydrogenation catalyst is prepared by an acid-base co-precipitation method, comprising the following steps: (1) adding a mixed solution of zinc nitrate, aluminum nitrate, copper nitrate, magnesium nitrate and silica sol and a precipitant A, citric acid, into a reactor in parallel, wherein the amount of the precipitant A, citric acid, is 30% to 100% of the stoichiometric amount required to form citrate with the added zinc nitrate, aluminum nitrate, copper nitrate and magnesium nitrate, and neutralizing and aging for 25 to 35 minutes in a reactor kept at 60 to 70° C. and stirred to obtain an aged solution; (2) without removing the mother liquor, the aged solution obtained in step (1) and the soluble carbonate of the precipitant B are directly added to the same reactor in parallel to be neutralized and aged again to form a coprecipitation solution; (3) The coprecipitation solution of step (2) is washed with water and filtered to obtain a filter cake, the filter cake is dried and calcined, and finally graphite is added to form a sheet to obtain a gas-phase aldehyde hydrogenation catalyst.

2. The use according to claim 1, characterized in that: The BET specific surface area of ​​the gas phase aldehyde hydrogenation catalyst is 30 m 2 / g~70m 2 / g, the pore volume is 0.15ml / g~0.8ml / g, and the average pore radius is 5nm~20nm.

3. The use according to claim 1, characterized in that: The amount of the soluble carbonate of the precipitant B added is adjusted to a pH value of 7 to 8 in the solution of step (2).

4. The use according to claim 1, characterized in that: In the step (3), the drying temperature is 100 to 120° C. and the drying time is 2 to 4 hours.

5. The use according to claim 1, characterized in that: In the step (3), the calcination temperature is 360-400° C. and the calcination time is 3-4 hours.

Citation Information

Patent Citations

  • Aldehyde gas phase hydrogenation catalyst and preparation method thereof

    CN102350360A

  • Preparation method of octylene aldehyde gas phase hydrogenation catalyst for octanol production

    CN102407122B

  • Improved aldehyde hydrogenation catalyst and process

    CN1050994A

  • Hydrogenation catalyst and method for producing same

    CN106132542A

  • Catalyst for preparing n-butyl alcohol by hydrogenation of n-butyl aldehyde and preparation method of catalyst

    CN108043411A